Synthesis and Kinetic Study of the Urea Controlled Release Composite Material: Sodium Lignosulfonate from Isolation of Wood Sawdust-Sodium Alginate-Tapioca - Arif Cahyo Imawan; Yehezkiel Steven Kurniawan; Muhammad Fernadi Lukman; Jumina Jumina; Triyono Triyono; Dwi Siswanta (Indonesian Journal of Chemistry, 2018)
A synthesis and kinetic study of the urea controlled-release composite material based on isolated Na-lignosulfonate, Na-alginate and tapioca was carried out. This experiment’s aims were to isolate Na-lignosulfonate from wood sawdust and to applicate this isolated Na-lignosulfonate, along with tapioca and Na-alginate as urea control release composite material. A kinetic study of urea released from the composite materials was also conducted. Na-lignosulfonate was isolated by Kraft lignin method to give a brown solid yield of 16.92% and was characterized by FT-IR spectrophotometer and SEM-EDX. The composite materials were synthesized by blending urea as the active compound with composite material as the carrier compound. Three types of material were prepared: complete material (A), low-concentration Na-lignosulfonate material (B) and material without tapioca (C). The composite material had a spherical form with 0.79 mm radius and 2.16 mm swollen radius. Urea content inside material was 40.425 mg urea/g material. The urea diffusivity coefficient for material A, B, and C were 7.27 x 10–6; 15.50 x 10–6 and 0.94 x 10–6 m2 h–1, respectively. Modelling analysis showed the experiment obeyed around only 15% of the Korsmeyer–Peppas model, but there was good correlation (80%) with the unsteady-state diffusion model.